STRATEGI PENYELESAIAN PEMBIAYAAN BERMASALAH PADA AKAD MURABAHAH DI BMT-UGT NUSANTARA CAPEM PESANGGARAN KABUPATEN BANYUWANGI - munawir nawir; Imam Husnudin; Nur Indah (Prodi Perbankan Syariah, Fakultas Ekonomi dan Bisnis Islam, Universitas Al Hikmah Indonesia, 2022)
The objectives of this study are: 1) To find out how the implementation of murabahah financing in BMT-UGT Nusantara Capem Pesanggaran Banyuwangi Regency. 2) to find out the factors causing the problematic financing of BMT-UGT Nusantara Capem Pesanggaran Banyuwangi Regency. 3) to find out the Settlement strategy carried out by BMT-UGT Nusantara Capem Pesanggaran in overcoming the problematic financing. The type of research used is descriptive research with a qualitative approach. Primary data sources in the form of interviews. Data collection techniques observation, interviews, and documentation. The data analysis technique used is interactive model. The object of this study is the strategy for handling problematic murabahah financing / often known as bad credit in murabahah financing of Islamic financial institutions. Meanwhile, the research subjects were the head of the BMT and two members of the AOP. The results explain that the financing procedures applied in BMT-UGT Nusantara Pesanggaran Head of Banyuwangi Regency on the practice of murabahah financing can be said to have been good, because in its implementation everyone who wants to become a murabahah financing customer at BMT-UGT Nusantara Pesanggaran Head of Banyuwangi Regency, must meet the applicable requirements and procedures, the factors that influence cause financing problems, namely the existence of internal and external factors, the strategy for handling problematic murabahah financing at BMT-UGT Nusantara Capem Pesanggaran Banyuwangi Regency uses a rescheduling strategy (re-scheduling), reconditioning (requirements), and the last step if it does not work is the execution step (seizure of collateral). ). The conclusion based on the data above is that the performance of BMT-UGT Nusantara Capem Pesanggaran in dealing with problematic murābaḥah financing is in accordance with the Fatwa of the National Sharia Council of the Indonesian Ulema Council.